Potential of Forest Bird Diversity and Abundance in Tretes Waterfall, Wonosalam as an Avitourism Location - Muhammad Zahrudin Afnan; Monica Salma Fitriandini; Mahendra Ekalukmana Firmansyah (Jurnal Biologi Tropis, 2022)
Tretes Waterfall is an avitourism area because it is located in the Raden Soerjo Grand Forest Park area. The diversity of bird species is very abundant there, especially forest birds. The diversity and abundance of birds are influenced by the condition of the forest which is still beautiful and the availability of various types of trees and other living things as a source of food for a bird. The purpose of this research To analyze the potential diversity and abundance of forest birds in Tretes waterfall, Wonosalam as an avitourism location and Analyzing the carrying capacity of management as Tretes Waterfall, Wonosalam, an avitourism location. The study was carried out from June to September 2021. The method used is the IPA (Index Point of Abudance) method, namely bird data collection is carried out at a certain time where there are 4 observation points and the rapid assessment method. The species of birds found in Tretes Waterfall, Wonosalam were 45 species with the abundance value of bird species at the observation point of residential residents categorized as general. While the abundance of bird species at the observation points of post 1, post 2, and waterfalls is in the frequent category (2.1-10,0). Tretes Waterfall has the potential to be developed as an avitourism area. More in-depth research can be carried out to determine the spatial and temporal distribution of birds in Tretes Waterfall so that avitourism is easier to develop.